A study of The effect of the aqueous extract of different organs of Peganum harmala L. on the germination and growth of Amaranthus retroflexus L. and Chenopodium album L. - Reza Rezvani; Alireza Dadkhah (علوم و فناوری بذر ایران)
This research was conducted in order to investigate the effect of aqueous extract of different organs of harmel (Peganum harmala) on the growth and germination of Amaranthus retroflexus and Chenopodium album in two experiments (laboratory and greenhouse) respectively, based on CRD with three replications and RCBD with four replications. The treatments included aqueous harmel extracts in concentrations of 10% and 20% root, 10% and 20% Aerial organ and control. with increasing extract concentration, the growth traits and total chlorophyll of both plants decreased significantly. The highest and lowest levels of inhibition rates were associated with 20% stem extract and 10% root extract, respectively, but total soluble sugars and antioxidant activity of weeds increased with increasing levels of harmel root and stem extract. shoot extract decreased the germination speed in Chenopodium and Amaranthus by 87.35% and 91.22%, respectively, compared to the control. In Amaranthus the length index of the plant by 63.33% and 96.67% respectively. the highest root and shoot concentrations (20%) decreased. The length of root by 50.49 and 86.94%, In Amaranthus and 47.87 and 81.80% in Chenopodium compared to the control. The highest total soluble sugar was observed at the level of 20% of the stem, and Amaranthus had more total soluble sugar with an increase of 64.9% compared to the control. Most traits in Amaranthus were more sensitive to the allelopathic effects of harmel compared to Chenopodium. extract of shoot was stronger than the root extract, which can be used in the preparation of herbicides with natural sources.